Psychometric Analysis of the State Metacognitive Inventory in University Students from City of Arequipa, Peru - Arias Gallegos, Walter (Universidad Estatal a Distancia, 2025)
In this psychometric research, the internal structure and reliability of the Metacognitive Strategies Inventory by O'Neil and Abedi (1996) were analyzed in a sample of university students from Peru. For this purpose, an intentional sample of 404 students from a private university in the city of Arequipa was taken, of which 54.5% were men with an average age of 19 years. The version of the test validated by Vallejos et al. was applied. (2012) which has a three-factor structure: Self-knowledge, Self-regulation and Evaluation. To calculate the validity of the instrument, confirmatory factor analysis was applied, and to calculate reliability, Cronbach's Alpha test and McDonald's Omega test were applied. The results corroborated the three-factor structure, but only the first dimension obtained adequate reliability indices.